The Use of Raw Rice Husks to Enhance Clay Bricks Strength for Building Construction - Said Ahmad Rafiuddin Said Sultan (School of Environmental Engineering, University Malaysia Perlis, 2016)
To prepare a clay brick for the building construction using the raw rice husks. To study the physical properties of the modified clay brick using the raw rice husks. To determine the engineering properties of the modified clay brick using the raw rice husks.